2004
DOI: 10.1021/ja039890j
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Stability of N-Heterocyclic Carbenes in Water:  The Carbon Acid pKaof Imidazolium Cations in Aqueous Solution

Abstract: We report second-order rate constants kDO (M-1 s-1) for exchange for deuterium of the C(2)-proton of a series of simple imidazolium cations to give the corresponding singlet imidazol-2-yl carbenes in D2O at 25 degrees C and I = 1.0 (KCl). Evidence is presented that the reverse protonation of imidazol-2-yl carbenes by solvent water is limited by solvent reorganization and occurs with a rate constant of kHOH = kreorg = 10(11) s-1. The data were used to calculate reliable carbon acid pK(a)s for ionization of imid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
407
2
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 491 publications
(445 citation statements)
references
References 70 publications
(122 reference statements)
23
407
2
4
Order By: Relevance
“…Evidence was presented in earlier work by Amyes et al 22 and us 24 The k DO values in Table 1 Although the k p /k reorg ratios clearly illustrate that re-protonation of thiazolylidenes and solvent reorganization occur at similar rates, Washabaugh and Jencks state that the extent of internal return should be interpreted conservatively because the errors are ± 30% or more. 29 For the determination of a pK a value for N-cyanomethylthiazolium salt 24…”
Section: Estimation Of Pk Amentioning
confidence: 77%
See 4 more Smart Citations
“…Evidence was presented in earlier work by Amyes et al 22 and us 24 The k DO values in Table 1 Although the k p /k reorg ratios clearly illustrate that re-protonation of thiazolylidenes and solvent reorganization occur at similar rates, Washabaugh and Jencks state that the extent of internal return should be interpreted conservatively because the errors are ± 30% or more. 29 For the determination of a pK a value for N-cyanomethylthiazolium salt 24…”
Section: Estimation Of Pk Amentioning
confidence: 77%
“…The kinetic acidities towards deprotonation of all triazolium ions by deuteroxide ion via Pathway A (k DO , Table 1) are significantly higher than for analogous imidazolium, 22,24 4,5-dihydroimidazolium 24 and thiazolium ions 27 The triazolium salts in Table 1 are also substantially more acidic than any thiazolium salt studied to date under similar reaction conditions, although the latter experiments have been limited to N-alkyl substituted examples. 27 We have measured a suggested that the more electron withdrawing N-pentafluorophenyl triazolium salts are more acidic than the corresponding N-mesityl salts.…”
Section: Substituent Effects On Kinetic Acidities Towards Deuteroxidementioning
confidence: 95%
See 3 more Smart Citations